Playing for Life. Fun and active games to develop children's skills, confidence and lifelong interest in sport (Australian Sports Commission, 2019)
Playing for Life activity cards are designed for everyday use by teachers, coaches, out of school hours care staff and parents. Aligned with the Australian Curriculum and the Australian Physical Literacy Framework, these game based activities are easily adapted to different sports and help create a safe, inclusive and challenging environment for children.